Pelatihan Dasar Full-Stack Programming Network Bagi Siswa Smk Bintang Nusantara : bahasa indonesia - Iis Istiqomah; Sutrisno; okta irawati (CV. Multi Kreasi Media, 2022)
Analysis of the situation based on observations in the field regarding the profile of the Bintang Nusantara Vocational School during this pandemic, namely the lack of learning materials and the provision of knowledge gained by students. Many students have scores below the minimum average in the vocational competency unit. Values ​​below the average will have difficulty taking the school exam in theory and practice. For students who have a minimum competency value, it will be difficult to find a job later. With a less than average graduation rate, it will have an impact on the school's own accreditation value. The justification for the proposer and partners in determining the priority issues that have been agreed to be resolved during the implementation of the PkM program is the Basic Full-Stack Programming Network Training for SMK Bintang Nusantara Students.